Archean-Mesoproterozoic Crustal Evolution and Crust-Mantle Geodynamics of Western Liaoning-Northeastern Hebei Provinces, North China Craton - Wang, Wei (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This thesis presents geological, petrological, geochemical, and zircon U-Pb-Lu-Hf isotopic field data for representative Precambrian lithologies in the Western Liaoning-Northeastern Hebei Provinces along the northern margin of the North China Craton (NCC). It describes late Neoarchean (2.64-2.48 Ga) supracrustal metavolcanic rocks and granitoid gneisses; late Paleoproterozoic (1.72-1.68 Ga) Jianping alkaline plutons and Pinggu alkaline volcanic rocks; and newly discovered ~1.23 Ga mafic dykes. The nature of magma sources and genesis of each magmatic episode are investigated, and the Precambrian (~2.6-1.2 Ga) lithospheric mantle evolution and crust-mantle interaction processes are established for the first time -aspects that provide important constraints in our understanding of the Precambrian crustal evolution and geodynamic processes in the region studied.